Assessment center y selección de personal (2020)
This paper analyzes the relationship between the staff pick within a company and one of the methodologies used to develop them, called Assessment Center. Where the different specific techniques can be compared by this recruitment model, We will also show how organizations benefit from an adequate personnel selection process. It begins with a brief introduction to the term, its origin and how its concept has evolved over the years. The purpose of this research is to demonstrate and detail the importance of the Assessment Center as a solution to start a good person selection process, that through a series of exercises allows us to profile and evaluate the conditions and skills of an applicant to determine if it meets the requirements requested to fill a position determined by the organization